Про розв’язання двовимiрних крайових задач статики некругових цилiндричних оболонок в уточненiй постановцi iз застосуванням сплайн-функцiй - Яремченко, C.M. (Видавничий дім "Академперіодика" НАН України, 2007)
The aspects of applications of the spline method and the discrete orthogonalization method to the solution of 2D boundary-value problems on a stress-strain state of noncircular cylindrical shells in a refined formulation are analyzed. The accuracy of solutions is estimated.